Headache and GLP-1 receptor agonists: when medications are therapeutic and when they contribute to the symptom - Ferreira, Erika Tavares; Garcia, Leidys Marina Pedrozo; Londero, Renata Gomes (Arquivos de Neuro-Psiquiatria, 2025)
Obesity is a complex metabolic disorder with significant implications for both individual and public health. It has been strongly linked to chronic headache conditions, including migraines and idiopathic intracranial hypertension (IIH). Individuals with obesity who suffer from migraine are at increased risk of chronification, while weight reduction has been associated with improvement in IIH-related headaches, likely due to a decrease in cerebrospinal fluid pressure. These observations underscore the importance of weight management strategies as a therapeutic consideration in patients with obesity and headache disorders. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are pharmacological agents that mimic the hormone's endogenous activity. Analysis of selected studies highlights that these agents have emerged as a promising therapeutic option. The aim of this narrative review is to examine the role of GLP-1 RAs in the management of headaches, particularly in the context of IIH, migraine, and the gut–brain axis. Additionally, this review addresses the challenges associated with the use of this pharmaceutical class, including the potential for headaches as adverse effect, and identifies existing knowledge gaps that may guide future research.
Keywords: Glucagon-Like Peptide-1 Receptor Agonists; Headache Disorders; Obesity; Migraine Disorders